HOMEMADE TERRORISM - Grząślewicz, Tomasz; Wojtasik, Karolina (No Limits, 2022)
Terrorism is a method of action, and the radicalisation which may lead to violence is not necessarily linked to Islam or its ideology’. While Islamist terrorist organisations such as Al-Qa'ida or ISIS are responsible for most of the attacks we hear about in the media, the 2011 attacks in Norway were carried out by a right-wing extremist Anders Breivik, a blond-haired and blue-eyed man. The article is devoted to the analysis of the motivations and modes of conduct of terrorists.